Beware of your teaching style: A school-year long investigation of controlling teaching and student motivational experiences. (February 2018) - Bartholomew, Kimberley J.; Ntoumanis, Nikos; Mouratidis, Athanasios; Katartzi, Ermioni; Thøgersen-Ntoumani, Cecilie; Vlachopoulos, Symeon
Abstract: Relatively little research drawing from self-determination theory has examined the links between controlling teaching environments and student motivation. To this end, two longitudinal studies were conducted to explore how students' perceptions of controlling teaching behavior and experiences of psychological need frustration were associated with a number of motivation-related outcomes over a school year. Multilevel growth modelling indicated that changes in perceptions of controlling teaching positively related to changes in need frustration across the school year (Studies 1 & 2) which, in turn, negatively related to autonomous motivation and positively related to controlled motivation and amotivation in Study 1 ( N = 419); and positively related to fear of failure, contingent self-worth, and challenge avoidance in Study 2 ( N = 447). Significant indirect effects also supported the mediating role of need frustration. These findings reinforce the need for research on the negative motivational pathways which link controlling teaching to poor quality student motivation. Implications for teacher training are discussed. Highlights: Perceived controlling teaching was associated with poor quality student motivation. Need frustration mediated relations between controlling teaching and outcomes. This pattern of associations was observed across a whole school year. Findings highlight the value of studying negative motivational pathways in schools.